Advancing histone deacetylase 6 (HDAC6) as a promising therapeutic target for Alzheimer’s disease: from molecular insights to clinical prospects - Zhang, Wei; Zhang, Yueyang; Wang, Yanli; Wang, Changning; Zhang, Can (Frontiers in Drug Discovery, 2025)
Alzheimer’s disease (AD) is a worldwide neurodegenerative disorder and the leading cause of dementia. Despite decades of research which has improved the understanding of AD, an effective disease-modifying therapy has yet to be developed that can prevent, stop, or reverse neuropathological changes and cognitive deficits of AD. There has been keen interest in targeting the epigenetic protein histone deacetylase 6 (HDAC6) for various human conditions leveraging its pathophysiological functions. Particularly, the pathological hallmarks of AD are aging-related accumulation of β-amyloid (Aβ) plaques and tau protein-related neurofibrillary tangles. In preclinical studies, HDAC6 inhibitors may significantly improve Aβ clearance and decrease tau aggregation and genetic deficiency of HDAC6 ameliorates cognitive deficits in mouse models of AD. While some pan-HDAC inhibitors have been FDA-approved for certain clinical indications, many HDAC6 inhibitors exhibit therapeutic potentials in preclinical studies of AD, for which we prepare this article to review and discuss recent studies and offer prospectives. We envision that the field of drug discovery of HDAC6 in AD may benefit by leveraging multimodal approaches, including structural and computational biology, medicinal chemistry, neuropathology and biomarker discovery. Using these approaches, future research will be better poised to efficiently discover new and potent HDAC6-selective inhibitors with enhanced blood-brain-barrier penetration, desirable safety and anti-AD efficacy. Considering the accumulated findings of HDAC6 and the urgent need in the field of AD, we speculate that many new small molecule inhibitors of HDAC6 will move forward enabling translational and clinical evaluations as potential therapeutics of AD.